The forbidden room [videorecording (DVD)] - Maddin, Guy, 1956-; Dupuis, Roy, 1963-; Furey, Clara, 1983-; Negin, Louis; Amalric, Mathieu, 1965-; Rampling, Charlotte, 1946- (Kino Lorber, 2016)
A never-before-seen woodsman mysteriously appears aboard a submarine that's been trapped deep under water for months with an unstable cargo. As the terrified crew make their way through the corridors of the doomed vessel, they find themselves on a voyage into the origins of their darkest fears.